Decreasing Inappropriate Use of Mobile Devices in Urban High School Classrooms: Comparing an Antecedent Intervention With and Without the Good Behavior Game. Issue 3 (May 2019) - Hernan, Colleen J.; Collins, Tai A.; Morrison, Julie Q.; Kroeger, Stephen D.
As the capabilities of portable technology continue to advance and become more accessible, educators express concern about the impact of the inappropriate use of mobile devices on academic engagement and learning. An alternating treatments design was used to compare the effectiveness of an antecedent (Clear Box) intervention and an interdependent group contingency (Clear Box + Good Behavior Game [GBG]) intervention to typical classroom management techniques (Control) in increasing the academic engagement and decreasing mobile device use of high school students during instruction. The results indicate an increase in academic engagement and a decrease in the inappropriate presence of mobile devices in both classrooms with the implementation of the Clear Box + GBG, as compared with the Clear Box and Control conditions. In addition, teacher and student social validity data suggested that teachers and students viewed the Clear Box + GBG intervention favorably. Discussion focuses on contributions to the current literature, implications for practice, and suggestions for future areas of research.